Kedudukan Anak Lahir dari Teknologi Uterus Buatan dalam Perspektif Hukum Keluarga Islam di Indonesia - Hafiz Gilman Abdul Aziz; Uswatun Hasanah; Ghulam Ahmad Surya Negara; Argiya Athala Putri; Hasna Zahra Wahyuni; Abdul Rafi Ardiyanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of artificial womb technology raises complex legal questions regarding the status of children born through such technology within the framework of Islamic family law in Indonesia. This study aims to analyze the legal position of children born from artificial womb technology by examining normative Islamic legal principles, national regulations, and contemporary legal interpretations. Employing a normative juridical approach, this research reviews statutory provisions, including the Compilation of Islamic Law, marriage law, and relevant constitutional court decisions, alongside scholarly works on Islamic bioethics and maqāṣid al-sharī‘ah. The findings indicate that although Indonesian law has not explicitly regulated artificial womb technology, children born through this method may obtain full legal recognition provided that genetic lineage and lawful parental intent can be clearly established. The application of maqāṣid al-sharī‘ah, particularly the protection of lineage, dignity, and property, supports the recognition of civil rights, inheritance rights, and parental responsibilities toward such children. This study concludes that legal reform is necessary to ensure legal certainty and child protection in response to advances in reproductive technology, while maintaining harmony between scientific progress and Islamic legal values.